Necessity as a Juridic Category: A Working Hypothesis, by Jacopo Menochio (Italian Review of Legal History, 2024)
In the Trivulziana Library in Milan, the treatise De necessitate, eiusque privilegiis et prerogativis, by Jacopo Menochio, is preserved in a single voluminous manuscript.The method chosen by Menochio can be better understood through comparison with other sixteenth-seventeenth century treatises that deal with themes of the same transversal and complex nature (poverty, illness and the like).Although the work is incomplete, the reading reveals itself of considerable interest both in the first part, more refined and meditated, dedicated to the theoretical introduction on the philosophical-juridical concept of necessity, as in the much more confused and fragmentary part, in which the author planned to analytically analyze the numerous privilegia, which in the field of law are connected to the different conceptions and situations of necessity. The very disorganized nature of the code gives it a particularly significant: in addition to providing a sample of the juridic knowledge of the professor from Pavia, dealing with a concept of multiple theoretical and practical facets, the text offers an interesting vision of the working method with which a treatise on such a complex theme is being constructed, and shows us the way in which an illustrious jurist of the late ius commune era masters the immense mass of sources and reference authorities to reach the solution of every possible concrete case.
Keywords: Necessity; Jacopo Menochio; treatise; legal privilege.